The Impact of Aid on Human Development Indices in Sub-Saharan Africa - Tsokodayi, Jade Takudzwa (Graduate School of Business (GSB), 2021)
This study investigates the relationship between official development assistance (ODA) and human development indicators (HDIs) in 49 sub-Saharan African countries over the period of 1995 to 2017 using 3-stage least squares (3SLS). The four key sub-classes of HDIs considered for this research include education, health, government and civic society, as well as environmental indicators. Of all these HDIs, the results of the analysis show that health aid is the most effective form of aid, significantly reducing the incidence of HIV, the infant mortality rate and the maternal mortality rate, as well as leading to improved life expectancy. Education aid has a significant effect on the progression to secondary school followed by adult literacy rates. Government and civil society aid significantly affects the ability of girls to access education at primary, secondary and tertiary levels while environmental aid is found to increase the carbon efficiency of production. Hence, this study demonstrates that aid is most effective on the health, education and environmental human development indicators.